Palladium‐Catalyzed Annulation of Arylbenzamides with Diaryliodonium Salts. Issue 2 (2nd November 2021) - Pan, Cheng; Wang, Limin; Han, Jianwei
Abstract: By using diaryliodonium salts, a cylization has been accomplished in the synthesis of N ‐aryl phenanthridinone derivatives via a cascade of ortho ‐arylation and C sp 2 ‐N bond formation in the presence of palladium catalyst. The reaction exhibits a broad compatibility of readily available N ‐arylnaphthamides. Abstract :